Alterations in Skeletal Muscle Cell Homeostasis in a Mouse Model of Cigarette Smoke Exposure - Caron, Marc-André; Morissette, Mathieu C.; Thériault, Marie-Eve; Nikota, Jake K.; Stämpfli, Martin R.; Debigaré, Richard (PloS one, 2013)
Skeletal muscle dysfunction is common in chronic obstructive pulmonary disease (COPD), a disease mainly caused by chronic cigarette use. An important proportion of patients with COPD have decreased muscle mass, suggesting that chronic cigarette smoke exposure may interfere with skeletal muscle cellular equilibrium. Therefore, the main objective of this study was to investigate the kinetic of the effects that cigarette smoke exposure has on skeletal muscle cell signaling involved in protein homeostasis and to assess the reversibility of these effects. A mouse model of cigarette smoke exposure was used to assess skeletal muscle changes. BALB/c mice were exposed to cigarette smoke or room air for 8 weeks, 24 weeks or 24 weeks followed by 60 days of cessation. The gastrocnemius and soleus muscles were collected and the activation state of key mediators involved in protein synthesis and degradation was assessed. Gastrocnemius and soleus were smaller in mice exposed to cigarette smoke for 8 and 24 weeks compared to room air exposed animals. Pro-degradation proteins were induced at the mRNA level after 8 and 24 weeks. Twenty-four weeks of cigarette smoke exposure induced pro-degradation proteins and reduced Akt phosphorylation and glycogen synthase kinase-3β quantity. A 60-day smoking cessation period reversed the cell signaling alterations induced by cigarette smoke exposure. Repeated cigarette smoke exposure induces reversible muscle signaling alterations that are dependent on the duration of the cigarette smoke exposure. These results highlights a beneficial aspect associated with smoking cessation.